Estimating Recommended Gonorrhea and Chlamydia Treatment Rate Using Linked Medical Claims, Prescription, and Laboratory Data in US Private Settings. Issue 3 (30th March 2021) - Tao, Guoyu; Workowski, Kimberly; Bowden, Katherine E.; Pearson, William S.; Sullivan, Jane M.; Henk, Henry J.; Gift, Thomas L.
Abstract : Analysis of treatment claims that medical records from private settings indicated low rates of recommended gonorrhea and chlamydia treatment. Abstract : Background: The Centers for Disease Control and Prevention (CDC) recommends specific regimens for chlamydia and dual therapy for gonorrhea to mitigate antimicrobial-resistant gonorrhea in the CDC 2015 sexually transmitted disease treatment guidelines. Only limited studies examining adherence to these recommendations have been conducted at private practices in the United States. Methods: We used the OptumLabs Data Warehouse, a comprehensive, longitudinal data asset with deidentified persons with linked commercial insurance claims and clinical information, to identify persons aged 15 to 60 years who had valid nucleic acid amplification testing results demonstrating urogenital or extragenital gonorrhea or chlamydia in 2016 to 2018. We defined valid laboratory results as positive or negative. We then assessed the time of their first positive test result and the type of treatment within 30 days to determine if there was evidence in the claims record that the CDC-recommended treatment was provided. We defined presumed treatment if the date of treatment was before the date of the positive test result within 30 days. Results: Among 6476 patients with positive gonorrhea test results and 26, 847 patients with positive chlamydia test results only, 34.8% and 64.2% had evidence of receiving the CDC-recommended therapy, respectively. Approximately 11.6% of patients with positive gonorrhea test results with recommended dual treatment and 7.1% of patients with positive chlamydia test results only with recommended chlamydia treatment were presumptively treated. Conclusion: Analysis of treatment claims and medical records from private settings indicated low rates of recommended gonorrhea and chlamydia treatment. Validation of treatment claims is needed to support further quality of care interventions based on these data.